The French road movie : space, mobility, identity - Archer, Neil, 1971- (Berghahn Books, 2013)
The traditionally American genre of the road movie has been explored and reconfigured in the French context since the later 1960s. Comparative in its approach, this book studies the inter-relationship between American and French culture and cinemas, and in the process considers and challenges histories of the road movie. It combines film history with film theory methodologies, analyzing transformations in social, political and film-industrial contexts alongside changing perspectives on the meaning and possibilities of film. At once chronological and thematic in structure, The French Road Mo.